Postharvest quality maintenance and bioactive compounds enhancement in ‘Taaptimjaan’ wax apple during short-term storage by salicylic acid immersion - Supapvanich, Suriyan; Mitsang, Preyanuch; Youryon, Pannipa; Techavuthiporn, Chairat; Boonyaritthongchai, Panida; Tepsorn, Racha (My University, 2018)
Physicochemical quality and bioactive compounds of ‘Taaptipjaan’ wax apple (Syzygium samarangenese) that were immersed in 0, 0.5 and 1.0 mM salicylic acid (SA) for 30 min and then stored at 12 ± 1 °C for 9 days were investigated. SA had no effect on the colour of fruit skin, total soluble solids, total acidity, total sugars, ascorbic acid (AsA) and anthocyanin contents but could help maintaining the firmness of the fruit. Antioxidant activity, total phenols, total flavonoids and antioxidant enzymes activities such as peroxidase and catalase were enhanced by SA. The SA immersion at the concentration of 0.5 mM effectively maintained firmness and visual appearance without causing any shrinkage on the fruit top and skin pitting and enhanced the bioactive compounds greater than 1.0 mM SA immersion. The evidences suggest that 0.5 mM SA immersion is an effective approach of maintaining quality and enhancing bioactive compounds including the activities of antioxidant enzymes in the fruit during short-term storage.
Keywords: Bioactive compounds; Physicochemical quality; Salicylic acid; Wax apple fruit